Plant growth forms dictate adaptations to the local climate - dos Santos, Patrícia; Brilhante, Miguel Ângelo; Messerschmid, Thibaud F. E.; Serrano, Helena Cristina; Kadereit, Gudrun; Branquinho, Cristina; de Vos, Jurriaan M. (Frontiers in Plant Science, 2022)
Adaptive radiation is a significant driver of biodiversity. Primarily studied in animal systems, mechanisms that trigger adaptive radiations remain poorly understood in plants. A frequently claimed indicator of adaptive radiation in plants is growth form diversity when tied to the occupation of different habitats. However, it remains obscure whether morphological adaptations manifest as growth form diversity per se or as its constituent traits. We use the classic Aeonium radiation from the Canary Islands to ask whether adaptation across climatic space is structured by growth form evolution. Using morphological sampling with site-associated climate in a phylogenetic context, we find that growth forms dictate adaptations to the local environment. Furthermore, we demonstrate that the response of specific traits to analogous environments is antagonistic when growth forms are different. This finding suggests for the first time that growth forms represent particular ecological functions, allowing the co-occurrence of closely related species, being a product of divergent selection during evolution in sympatry.